A Comprehensive Overview in Control Algorithms for High Switching-Frequency LLC Resonant Converter - Park, Hwa-Pyeong; Kim, Mina; Jung, Jee-Hoon (Energies (Basel), 2020)
An LLC resonant converter has been widely used in various industrial applications because of its high cost-effectiveness, high power conversion efficiency, simple design methodology, and simple control algorithms using a pulse frequency modulation (PFM). In addition, the soft switching capability of the LLC resonant converter is good to obtain high switching frequency operations, which can get the high-power density of the power converter. Over the past years, several studies have been conducted to improve the performance of a high switching frequency LLC resonant converter with resonant tank design, optimal power stage design, and enhanced control algorithms. This paper is the review paper in terms of the control algorithms for the LLC resonant converter. It focuses on the overview of the high switching-frequency LLC resonant converter in terms of the control algorithms. The advanced control algorithm can improve power conversion efficiency, dynamic performance, tight output voltage regulation, and small electro-magnetic interference. The operational principles of the control algorithms are briefly explained to show their own characteristics and advantages. Thereafter, the research issues for the future works will be discussed in the conclusion.